Addressing financial and digital literacy challenges for inclusive finance: Insights from microfinance institutions and fintech organisations - Franziska Koefer; Amber Bokkens; Massimo Preziuso; Michel Ehrenhard (European Investment Fund (EIF), 2024)
This paper investigates strategies of European microfinance institutions (MFIs) and inclusive FinTech organisations to address financial and digital illiteracy among vulnerable customers. It reveals that both MFIs and FinTech organisations focus on personalised financial education, training and coaching but adopt distinct strategies in their approach.The study highlights the crucial role of support teams in enhancing literacy and recommends a balance between digitalisation and human interaction, alongside advocating for governmental and EU educational initiatives. This is the third paper resulting from a research project on 'Strengthening Financial Inclusion through Digitalisation' (SFIDE), initiated by EIF's Research & Market Analysis division. The project is funded by the EIB Institute under the EIB-University Sponsorship Programme (EIBURS). It aims to investigate the potential of technological and financial innovation to increase the efficiency of the inclusive finance sector, through the identification and promotion of best practices.
Keywords: 330; Finanzielle Inklusion; Finanzwissen; Digitale Kompetenz; Mikrofinanzierung; Finanztechnologie; EU-Staaten